2021
DOI: 10.1001/jamanetworkopen.2021.21410
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Use of a Price Transparency Tool for Childbirth Among Pregnant Individuals With Commercial Insurance

Abstract: This cross-sectional study examines the association between use of an insurance-owned patient-facing price estimator tool by pregnant individuals and out-of-pocket childbirth spending.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“… Identification of children with disabilities was based on an initial 24 months of continuous insurance 32 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… Identification of children with disabilities was based on an initial 24 months of continuous insurance 32 …”
Section: Resultsmentioning
confidence: 99%
“…This is a cross‐sectional, descriptive study of 133,749 person‐years of commercially insured data from 89,987 unique 0‐ to 18‐year‐olds with disabilities between January 1, 2012, and December 31, 2016. This study population was identified from 3,131,954 person‐years of data on 1,774,948 unique 0‐ to 18‐year‐old enrollees who were insured for at least 24 months 32 . Children with disabilities were identified the validated CWDA 1–3 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggest that price information may help individuals anticipate their out-of-pocket childbirth costs. 17 These more recent studies all vary in degree of impact, but most are showing directionally positive and significant consumer response to price transparency tools. The timetable for implementation of the new federal policies on transparency has been staggered over several years.…”
Section: Policy Backgroundmentioning
confidence: 99%
“…A 2017 study found that only 1% of patients who consumed advanced imaging services had used a new price-shopping tool (Desai et al, 2017). A 2022 study focusing on childbirth services found 13% of pregnant individuals using a price tool (Gourevitch et al, 2021).…”
Section: Introductionmentioning
confidence: 99%